Nanostructures as Photothermal Agents in Tumor Treatment - Chen, Yuqian; Zhou, Futing; Wang, Chenshuai; Hu, Linlin; Guo, Pengfei (Molecules (Basel, Switzerland), 2022)
Traditional methods of tumor treatment such as surgical resection, chemotherapy, and radiation therapy have certain limitations, and their treatment effects are not always satisfactory. As a new tumor treatment method, photothermal therapy based on nanostructures has attracted the attention of researchers due to its characteristics of minimally invasive, low side effects, and inhibition of cancer metastasis. In recent years, there has been a variety of inorganic or organic nanostructures used in the field of photothermal tumor treatment, and they have shown great application prospects. In this paper, the advantages and disadvantages of a variety of nanomaterials/nanostructures as photothermal agents (PTAs) for photothermal therapy as well as their research progress are reviewed. For the sake of clarity, the recently reported nanomaterials/nanostructures for photothermal therapy of tumor are classified into five main categories, i.e., carbon nanostructures, noble metal nanostructures, transition metal sulfides, organic polymer, and other nanostructures. In addition, future perspectives or challenges in the related field are discussed.